Estudo sobre compostagem e mini horta doméstica, seus benefícios socioambientais, e aplicação dos conceitos envolvidos por meio de uma sequência didática desenvolvida para alunos do Ensino Médio. - Erica Trevelin Antunes (2022)
Waste disposal is a problem for all sectors of society. Landfills are high-cost solutions with limited capacity. Composting is a process that can prolong the useful life of landfills, as half of the materials destined for landfills are organic matter of domestic origin. In addition, the compost product is na excellent quality fertilizer.This work proposes a didactic sequence related to the theme of composting and mini home garden to be used by teachers of the 1st year of high school, remotely. Students will be encouraged to set up their own compost bin and, later, a mini vegetable garden. Both will be made from easily accessible materials. Using the fertilizer produced in the composters, it is expected that students can verify and explain possible differences in plant development.The work also favors learning and understanding of the biological processes involved in composting, in the cultivation of the mini vegetable garden with the fertilizer produced, and discusses the associated socioeconomic aspects.